Data-driven reliability and availability of electronic equipment - Pokorni, Slavko J. (Vojnotehnički glasnik / Military Technical Courier, 2023)
Introduction/purpose Reliability and availability are important especially for military, medical, and other professional equipment. Reliability and availability management and/or prognostic reliability calculations have always been data  driven. This article focuses on the analysis of the data impact on reliability and availability.Methods: This research is based mostly on the articles published by the author of this work as well as on some other papers.Results: This paper results in a discussion on the definition of the data-driven concept, preceded by brief definitions of reliability and availability, and followed by the analysis of the main impacts of uncertain data on prognostic reliability calculations as well as by reliability and availability of data used in reliability calculations.Conclusions: Reliability and availability are still very important. Reliability and availability have always been data driven while valid and relevant data have always been the main problem. Without good data, prognostic reliability is useless in spite of a good reliability model.
Keywords: data driven; reliability; availability; data; equation